2013
DOI: 10.5455/ovj.2013.v3.i1.p64
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and type of toenail tumors in the dromedary camel

Abstract: A total of 275 dromedary camels (16 males and 259 females) of local “Arabiyat” breed suffering from different types and degrees of severity of toenail tumors were surgically treated. Histopathological examination of the tissue samples removed from 50 tumor-like growths (2 males and 48 females) revealed three types of tumors; squamous cell carcinoma (70%), spiny keratoderma (22%) and fibroma (8%). An increased incidence of tumors was recorded in the medial when compared to the lateral toenails in both sexes. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…These cords formed from concentrically laminated masses of intensely eosinophilic keratin in the center surrounded by peripheral polyhedral neoplastic cells. These findings were in partial agreement with that reported by Siddiqui et al, (2013) who found squamous cell carcinomas were the most common tumors in the medial toenails of the forelimbs in dromedary camel. Interestingly, two different types of SCC were reported in camels; well-differentiated and poorly differentiated types were distinguished from each other by horn pearls in the center whereas, in the poorly differentiated type, no horn pearls could be observed (Al-sobayil and El-amir, 2013).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These cords formed from concentrically laminated masses of intensely eosinophilic keratin in the center surrounded by peripheral polyhedral neoplastic cells. These findings were in partial agreement with that reported by Siddiqui et al, (2013) who found squamous cell carcinomas were the most common tumors in the medial toenails of the forelimbs in dromedary camel. Interestingly, two different types of SCC were reported in camels; well-differentiated and poorly differentiated types were distinguished from each other by horn pearls in the center whereas, in the poorly differentiated type, no horn pearls could be observed (Al-sobayil and El-amir, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…Cutaneous neoplasms have been reported as sporadic cases in camels. A case report of squamous cell carcinoma (Al-Sobayil and El-Amir, 2013; Siddiqui et al, 2013;Alsobayil et al, 2018) basal cell carcinoma (Al-Hizab et al, 2007), fibropapilloma (Oryan et al, 2011), fibroma, lipoma and fibromyxosarcoma (Al-Sobayil and Elamir, 2013), lipoma at ischiorectal fossa underneath the skin in the left side of the perianal area (Kaswan et al, 2013), squamous papillomas, fibropapillomas, sebaceous adenomas, melanocytomas and malignant melanoma (Khordadmehr et al, 2016) and cases of cutaneous papillomatosis in Saudi Arabia (Khalafalla et al, 2017), in Sudan (Ure et al, 2011;Khalafalla et al, 2018) has been described in dromedary camels. The classification of skin tumors is difficult due to the complex structure, and the ectodermal and mesodermal origin of skin components, in association with structural and physiological peculiarities of the skin in different animal species and breeds (Baba and Câtoi, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…SCC of the digits in camels from the Middle East are common and described to start as a solid, raised skin mass that if not addressed, expands to surrounding soft tissue structures and becomes ulcerative with proliferative granulation tissue 9,10 . The patient described in this report presented at the chronic stage of ulceration and exuberant granulation tissue in addition to pre‐scapular lymphadenopathy.…”
Section: Discussionmentioning
confidence: 88%
“…Neoplasia has been infrequently reported in Old World camelids. Documented neoplasms in the dromedary camel include nailbed squamous cell carcinoma, carpal chondrosarcoma, renal cell carcinoma, ovarian teratoma, lymphocytic leukemia, squamous cell carcinoma in the maxilla, and bronchoalveolar adenocarcinoma (6)(7)(8)(9)(10)(11)(12). In the Bactrian camel, reported tumors are limited to histiocytic sarcoma, meningioma, and gastric adenocarcinoma (13,14).…”
Section: Introductionmentioning
confidence: 99%